LEGAL PROTECTION OF UNMEET ANNUAL LEAVE RIGHTS FOR CERTAIN TIME WORKERS - Nadila Devita (Fakultas Hukum Universitas Djuanda Bogor, 2022)
In a company that produces plastic household items, workers' rights for a certain period of time to leave annual leave are not fulfilled. The annual leave is only for permanent employees while certain time workers do not get the right to annual leave. The purpose of this research is to determine legal protection of workers' annual leave rights for a certain period of time and legal solutions that workers can take if their annual leave is not fulfilled. This research uses a normative juridical research with a statutory approach (statue approach). The results of this study show that the legal protection of the right to annual leave for certain time workers has been regulated in Law No.13 of 2003 on Manpower and Law Number 11 of 2020 concerning Job Creation stipulates that certain time workers are entitled to annual leave when they have worked. in a company for 1 consecutive year, but if annual leave is not granted then one of the workers' rights for a certain time is not fulfilled and the company can be subject to criminal sanctions or fines and for legal settlement of non-fulfillment of annual leave, workers can complete it through non-fulfillment channels. litigation, namely bipartite, mediation, conciliation and arbitration or through litigation, namely through industrial relations courts.